The regularization landmarket and the implementation gives occupation Social gives city - Marques Rossetto, Adriana; de Souza da Silva, Andressa; Terezinha Uvo Bodnar, Roberta; Bodnar , Zenildo (Seven Editora, 2023)
The present work aims to analyze land tenure regularization and its effects on realization of the social function of the city, through the foundations established by the City Statute. Seeks to demonstrate the multidimensional interest in the implementation of land regularization, from the perspective of protecting the interests of the collectivity and the paradigm of Democratic state. To do so, the following research problem was started: Is land regularization an instrument for realizing the social function of the city? As research methodology, the inductive method was used and, in the data processing phase, the Cartesian method. In the different phases of the research, the techniques of the referent, gives category, concept operational and gives search bibliographic. DOI: 10.56238/pacfdnsv1-123